Prognostic Impact of Metabolic Syndrome in Patients With Heart Failure: A Meta-Analysis of Observational Studies - Huang, Zhuo-Ming; Chen, Wen-Rong; Su, Qi-Wen; Huang, Zhuo-Wen (Frontiers in Cardiovascular Medicine, 2021)
Background: The metabolic syndrome (MS) is significantly associated with the risk of incident heart failure (HF). However, there are still great controversies about the impact of MS on the prognosis in patients with established HF. This meta-analysis aimed to ascertain the effect of MS on the prognosis in patients with HF. Methods: We searched multiple electronic databases, including PubMed, Opengrey, EMBASE, and Cochran Library, for potential studies up to February 15, 2021. Observational studies that reported the impact of MS on the prognosis in patients with established HF were included for meta-analysis. Results: Ten studies comprising 18,590 patients with HF were included for meta-analysis. The median follow-up duration of the included studies was 2.4 years. Compared with HF patients without MS, the risk of all-cause mortality and cardiovascular mortality was not increased in HF with MS (HR = 1.04, 95% CI = 0.88–1.23 for all-cause mortality; HR = 1.66, 95% CI = 0.56–4.88 for cardiovascular mortality, respectively). However, there was a significant increase in composited cardiovascular events in the HF patients with MS compared with those without MS (HR = 1.73, 95% CI = 1.23–2.45). Conclusions: In patients with established HF, the presence of MS did not show an association on the risk of all-cause mortality or cardiovascular mortality, while it may increase the risk of composite cardiovascular events.